Link of Infection Prevention Climate to Patient-Centered Care: Role of Workplace Safety and Risk Mitigation - Rumintang Marito D; Widianto S (Dove Medical Press, 2024)
Debora Rumintang Marito, Sunu Widianto Department of Management and Business, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Debora Rumintang Marito, Department of Management and Business, Universitas Padjadjar, Jl. Dipati Ukur No. 46, Bandung, Jawa Barat, 45363, Indonesia, Email deborarumintang@gmail.comBackground: Healthcare-associated infections pose a substantial threat to the quality of healthcare services. Consequently, it is imperative for hospital organizations to actively support an infection prevention climate, fostering workplace safety and risk mitigation, thereby promoting patient-centered care.Purpose: This study aims to explore the interconnectedness between the infection prevention climate, workplace safety, risk mitigation, and patient-centered care.Methods: A cross-sectional study design was employed, utilizing a questionnaire administered to 235 healthcare professionals in intensive care and inpatient units at Bandung Kiwari Regional General Hospital. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4 and SPSS 25.Results: The study revealed several significant relationships, including (1) between infection prevention climate and patient-centered care; (2) infection prevention climate and workplace safety; (3) workplace safety and patient-centered care; (4) infection prevention climate and patient-centered care mediated by workplace safety; (5) infection prevention climate and risk mitigation; (6) risk mitigation and patient-centered care; (7) and the relationship between infection prevention climate and patient-centered care mediated by risk mitigation.Conclusion: Infection prevention climate emerges as a crucial intangible value that hospital organizations can cultivate to shape workplace safety. This, in turn, encourages healthcare workers' compliance in implementing infection prevention controls as a form of risk mitigation, ultimately contributing to the provision of patient-centered care.Keywords: healthcare-associated infections, infection prevention climate, patient-centered care, workplace safety, risk mitigation